2023
DOI: 10.14309/ajg.0000000000002497
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult-Onset of Inflammatory Bowel Diseases Is Associated With Higher Utilization of Analgesics: A Nationwide Cohort Study

Rahul S. Dalal,
Bente Mertz Nørgård,
Floor D. Zegers
et al.

Abstract: Introduction: Patients with inflammatory bowel diseases (IBD) commonly require analgesic medications to treat pain, which may be associated with complications. We examined trends of analgesic use according to age of IBD onset. Methods: This nationwide cohort study included adults diagnosed with IBD between 1996-2021 in Denmark. Patients were stratified according to their age of IBD onset: 18-39 years (young adult), 40-59 years (adult), and 60+ years (ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…3 A recent study from Denmark showed that the use of opioids had not declined during the first year after IBD diagnosis between 1996 and 2021. 11 This applied to all age groups, however, elderly with IBD more commonly received analgesic prescriptions of every class and had a two-fold increased odds of receiving strong opioid prescriptions after IBD diagnosis when compared to adults. Corroborating these data are our findings of considerable opioid use among the elderly undergoing surgery for CD both prior to and 9 months after surgery.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…3 A recent study from Denmark showed that the use of opioids had not declined during the first year after IBD diagnosis between 1996 and 2021. 11 This applied to all age groups, however, elderly with IBD more commonly received analgesic prescriptions of every class and had a two-fold increased odds of receiving strong opioid prescriptions after IBD diagnosis when compared to adults. Corroborating these data are our findings of considerable opioid use among the elderly undergoing surgery for CD both prior to and 9 months after surgery.…”
Section: Notementioning
confidence: 99%
“…9,10 Additionally, analgesic use appears to vary by age group in the IBD population. 11 Regarding pain management in IBD, several questions are still left to be answered -which subpopulations of patients with IBD are at risk for chronic pain and chronic use of analgesics and what are the clinical consequences in these patients? Unfortunately, at present, there is a lack of specific strategies for pain management in IBD and a lack of clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%